2009
DOI: 10.1111/j.1365-2621.2008.01790.x
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial properties of grape seed extracts and their effectiveness after incorporation into pea starch films

Abstract: Chemical analysis and antimicrobial nature of grape seed extracts (GSE) and their Reisling Vitis vinifera L. application as fortificants for edible starch films were investigated. GSE possessed an antioxidant activity of 17.18 ± 1.29 mmol TROLOX equivalents g extract )1 and total phenolic content of 327.58 ± 7.24 mmol gallic acid equivalents g extract )1 mainly attributed to their flavonoid and phenolic acid composition determined by high-performance liquid chromatography accomplished to a diode array detector… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
111
2
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 165 publications
(126 citation statements)
references
References 26 publications
7
111
2
2
Order By: Relevance
“…Namely, polyphenols can penetrate the semipermeable bacterial membrane, reacting with the cytoplasm or cellular proteins. This potential is higher in GSE as phenolic acids are present in an undissociated form (Paulus, 1993;Corrales et al, 2009). Scalbert (1991) proposed that the antibacterial activity of tannins, compounds present in GSE, could be due to the inhibition of extracellular microbial enzymes.…”
Section: Carvacrol and Gse Minimal Inhibitory Concentrationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Namely, polyphenols can penetrate the semipermeable bacterial membrane, reacting with the cytoplasm or cellular proteins. This potential is higher in GSE as phenolic acids are present in an undissociated form (Paulus, 1993;Corrales et al, 2009). Scalbert (1991) proposed that the antibacterial activity of tannins, compounds present in GSE, could be due to the inhibition of extracellular microbial enzymes.…”
Section: Carvacrol and Gse Minimal Inhibitory Concentrationsmentioning
confidence: 99%
“…Another compound known by its AM properties is grape seed extract (GSE). This is a rich source of monomeric phenolic compounds such as (+)-catechins, (-)-epicatechin, (-)-epicatechin-3-o-gallate, gallic acid and dimeric, trimeric and tetrameric procyanidins, which have AOX (Kim & Thomas, 2007) and antibacterial properties (Corrales, Han, & Tauscher, 2009). The order of increasing AM activity reported for parts of the grape vine was flesh, whole fruit grape extracts, fermented fruit, fermented pomace, skin, leaves and seeds (Xia, Deng, Guo, & Li, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Also, recently Yerlikaya et al (50) investigated the use of GSE in batter coating of shrimp and concluded that the incorporation of GSE in batter materials could improve the chemical, microbiological, and overall quality of shrimp during storage. In 2009, GSE was shown to be effectively incorporated into edible pea starch film to reduce the growth of undesirable pathogens in meat, improving meat quality and extending its shelf life (9). GSE has been shown to have great antioxidant activities in meat products (5,21,32,50).…”
mentioning
confidence: 99%
“…Jang et al (7) also reported that the TS of a rapeseed protein/gelatin composite film decreased and the E increased after the addition of GSE, similar to our results. The reason for the decrease in TS and increase in E might be attributable to weak intermolecular interactions between PP molecules because of the phenolic acids present in GSE (17). Therefore, with the antimicrobial activity of the 4% PP/1% RA composite film containing GSE, it is suggested that 1% GSE is a suitable content for the antimicrobial PP film, along with the mechanical property of the film containing GSE.…”
Section: Resultsmentioning
confidence: 99%